Spirituality in a secular age: from Charlies Taylor to study of the Bible and spirituality - A. T. Lincoln (Acta Theologica)
This essay proposes that those engaged in the study of the Bible in relation to spirituality would benefit from awareness of Charles Taylor’s thinking in A Secular Age, which is a narrative not only about the emergence of the secular but also about the role of the spiritual in Western civilization. The essay indicates the significance of Taylor’s work for understanding the present context of the experience of spirituality. It then suggests some possible implications for how biblical perspectives on spirituality might be studied, highlighting Taylor’s category of the social imaginary. Finally, it reflects on the potential of Taylor’s work for those who are interested in dialogue between a spirituality rooted in biblical perspectives and contemporary forms of spirituality, focusing on his notion of “fullness.”